ACRONYMS IN TITLE WRITING OF STUDENT CREATIVITY PROGRAMS 2018 - Margono, Margono; Sabardilla, Atiqa; Prayitno, Harun Joko (Lire Journal (Journal of Linguistics and Literature), 2020)
The writing of the Student Creativity Program (SCP) titles has its appeal and uniqueness. One of which can be seen in the process of forming words in the form of acronyms. This article aims to describe the process and results of the formation of acronyms on the writing of SCP titles funded in 2018. This research is a qualitative descriptive study. This research data are in the form of words, phrases, clauses, and sentences in the SCP titles. The source of research data is the SCP titles from 5 fields in 2018. Data collection uses observation and note-taking techniques. The method of data analysis is the constituent analysis method and its expansion techniques, namely techniques of removing, inserting, replacing, and expanding. The data validity test uses theory triangulation. The results show that the formation of acronyms produced five forms of acronyms on the writing of the SCP titles, namely acronyms derived from two words, three words, four words, five words, and more than five words. Three acronym formation processes are found, namely using the initial letters of words, using syllables or fragments of words, and using mixes of initial letters of words and syllables or fragments of words.